The theory of Raymond Dyval mapped in the editions of the national Day of mathematical education (Research, Society and Development, 2021)
Scientific events are of fundamental importance for the dissemination of knowledge produced by science. Thus, this production aims to present an overview of research that uses Raymond Duval's Theory of Semiotic Representation Records as a theoretical contribution. The selected event was the National Day of Mathematical Education - JEM held by the University of Passo Fundo located in the state of Rio Grande do Sul. It is a biennial event, its first edition took place in 2006. Currently, JEM is in its eighth edition. The researches were analyzed in a quali-quanti way, the quantitative approach was used to analyze data such as nature of the research, level of education, among others, for the categorization of the researches in foci and subfocuses the qualitative approach was considered, for this the line methodology proposed by Dario Fiorentini. Nineteen works were found, which were divided into 04 thematic focuses and 06 subfocuses. It is also noteworthy that even though it is a national event, all works are restricted to the southern region.